2015
DOI: 10.4103/0019-5049.156868
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of propofol, sevoflurane and desflurane for neuroanaesthesia: A prospective randomised study in patients undergoing elective supratentorial craniotomy

Abstract: Background and Aims:Both inhalational and intravenous anaesthetic agents are being used for neuroanaesthesia. Clinical trials comparing “propofol and sevoflurane” and “desflurane and sevoflurane” have been published. However, the comparison of all the three anaesthetics in neurosurgical patients has not been done. A randomised clinical study was carried out comparing propofol, sevoflurane and desflurane to find the ideal neuroanaesthetic agent.Methods:A total of 75 adult patients undergoing elective craniotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…The incidence of agitation in our group of patients (13%) was within the range reported in previous studies (3% to 22%) [ 1 , 3 , 5 7 , 17 20 ] but markedly lower than that identified in our previous study (29%) [ 4 ]. Several changes to clinical practice in our institution were implemented after the completion of our previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…The incidence of agitation in our group of patients (13%) was within the range reported in previous studies (3% to 22%) [ 1 , 3 , 5 7 , 17 20 ] but markedly lower than that identified in our previous study (29%) [ 4 ]. Several changes to clinical practice in our institution were implemented after the completion of our previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…in their study on supratentorial lesions found comparable hemodynamics with propofol, sevoflurane, and desflurane. [ 2 ] In our study, we also found that intraoperative hemodynamics with respect to HR was comparable in both groups except at dura closure, skin closure, and removal of headpins. Although the difference in results of HR was statistically significant, the difference was clinically not important.…”
Section: Discussionsupporting
confidence: 73%
“…where they compared propofol, sevoflurane, and desflurane as a choice of anesthetic agent in patients undergoing elective supratentorial craniotomy. [ 2 ] In their trial in which each group had 25 patients, they did not find any appreciable difference in the relaxation of the brain with the use of any of the three agents ( P = 0.70).…”
Section: Discussionmentioning
confidence: 94%
“…[ 15 ] Propofol, sevoflurane and desflurane have the same and acceptable effects on the brain relaxation scores at various stages of surgery. [ 16 ] Dexmedetomidine is not sufficient to suppress haemodynamic responses but decreases the requirement of inhalation agents and provides brain relaxation and good surgical field exposure conditions without any side effect in patients undergoing supratentorial craniotomy. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%